2019
DOI: 10.1590/1983-21252019v32n316rc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Competition on the Interaction Between Maize and Weed Exposed to Water Deficiency

Abstract: The ability of plants to adapt to water deficient conditions in soil is directly related to the competitive ability of each species. The objective of the present study was to evaluate the effects of water deficiency and interspecific competition on the growth components of maize (Zea mays), brachiaria (Urochloa decumbens), and hairy beggarticks (Bidens pilosa L). The experimental design was in randomized blocks, with eight replications. The treatments were arranged in a 5 × 2 factorial design, with the first f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The reduction of stomatal conductance causes lower transpiration and, consequently, lower water loss, causing higher plant tolerance to water stress (DUTRA et al, 2015). This mechanism is an essential defense strategy, especially in semi-arid regions, where long periods occur without the occurrence of high-temperature rains (FREITAS et al, 2017;FREITAS et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of stomatal conductance causes lower transpiration and, consequently, lower water loss, causing higher plant tolerance to water stress (DUTRA et al, 2015). This mechanism is an essential defense strategy, especially in semi-arid regions, where long periods occur without the occurrence of high-temperature rains (FREITAS et al, 2017;FREITAS et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Easy dispersion and high seed production capacity allow both B. pilosa and B. subalternans to colonize cultivated and noncultivated areas (PAMPLONA et al, 2020). In addition, these species have a great capacity to extract water and nutrients from the soil, making these species good competitors for growth resources, during various crop cycles (SANTOS et al, 2015;FREITAS et al, 2019;SOARES et al, 2019). According to Deiss et al (2017), losses of productivity in the range of 30% in the soybean crop occurred due to the interference of B. pilosa and B. subalternans.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors observed that shoot dry matter of rye decreased by 37, 47 and 33% in water deficit conditions with interspecific and intraspecific competition, respectively. Freitas et al (2019) reported that there was competition for resources among maize, black-jack (Bidens pilosa) and signal grass (Urochloa decumbens), even when the amount of water in the soil was close to the field capacity. A decrease in growth due to either intra or interspecific competition results from spatial competition among plants.…”
Section: /9mentioning
confidence: 99%
“…on redroot pigweed depended on plant density; the larger the number of plants, the higher the shoot dry matter of the weed. Freitas et al (2019) showed that interspecific competition decreased the growth of corn and signal grass (Urochloa decumbens) plants and intensified negative effects of water deficit on these species.…”
Section: /9mentioning
confidence: 99%
“…Allelopathic chemicals restrict the crop growth and development of cereal crops ( Zea mays ) by producing phytotoxic chemicals ( Bhatt et al, 2001 ). Crop growth and development mainly depends on weed crop competition period, as competition period prolonged, it adversely influenced growth and development of crop ( Freitas et al, 2019 ). Durational interference of weeds significantly influences crop yield attributes as well as crop productivity ( Yaghoobi and Siyami, 2008 ).…”
Section: Introductionmentioning
confidence: 99%